Incentive systems for risky investment decisions under unknown preferences - Josef Schosser (Games, 2018)
Ortner et al. (Manage. Account. Res. 36(1):43-50, 2017) propose the State-Contingent Relative Benefit Cost Allocation Scheme as an incentive system for risky investment decisions. The note at hand reveals the information distribution implicitly assumed within the framework of this study. Based on this information distribution, both simpler and more powerful ways to induce consistency exist.
Keywords: D82; G31; M46; 330; investment decision; performance measure; relative benefit cost allocation